Respostas

2014-07-16T16:54:12-03:00
Z = (3-i)(2+2i)² / 3+i 

z = (3-i)(3-i)(2+2i)² / (3+i)(3-i) 

z = (3-i)(3-i)(2+2i)² / (9+1) 

z = (3-6i-1)(4+8i-4) / (9+1) 

z = (2-6i)(8i) / (10) 

z =(16i+48)/10 

z =24/5 +8i/5 

conjugado de z=24/5-8i/5 
2014-07-16T17:04:51-03:00
Z=  \frac{(3 - i)(2 + 2i)^2}{ 3 + i} ]
 z= ( \frac{(3 - i) (3 - i) (2 + 2i)^2}{(3 + i) ( 3-i)} ]
 z = ( \frac{(3 - i) (3 - i) (2 + 2i)^2}{(9 + 1)} ]
 z=  \frac{(3 - 6i - 1)(4 + 8i - 4)}{(9 + 1)} ]
 z=  \frac{(2 - 6i)(8i)}{10}  
z= \frac{16i + 48}{10}
z =  \frac{24}{5} +  \frac{8i}{5}

O Conjugado de z é  \frac{24}{5} +  \frac{8i}{5}

Abraços.
1 5 1